2022
DOI: 10.4314/jasem.v26i4.23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coarse Aggregate Size and Gradation on Workability and Compressive Strength of Plain Concrete

Abstract: In this study effect of coarse aggregate size and gradation on workability and compressive strength of concrete was investigated. A mix ratio of 1:2:4 with a target strength of 20/25MPa, was adopted with a water-cement ratio of 0.6. Concrete cubes were produced with uniform coarse aggregate size of 4.75, 6.7, 9.5, 13.2 and 19mm respectively, with another set of samples produced with all the coarse aggregate sizes. Slump tests were carried out for all mixes and all sets of samples were tested for compressive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…It has been reported that introduction of ceramic waste aggregate refines concrete pore structure and strengthen aggregate/cement paste bonding (Medina et al, 2012) and this is obviously the explanation for improved strength of RCT concrete. Moreover, there is a relationship between concrete strength and aggregate's shape, size and surface (Mkpaidem et. al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that introduction of ceramic waste aggregate refines concrete pore structure and strengthen aggregate/cement paste bonding (Medina et al, 2012) and this is obviously the explanation for improved strength of RCT concrete. Moreover, there is a relationship between concrete strength and aggregate's shape, size and surface (Mkpaidem et. al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…There was a significant influence from the coarse aggregate source on the compressive strength of various nominal mixed concrete plans (Prajapati, 2019). The compressive strength increases with increasing coarse aggregate size (Mkpaidem, 2022;Ogundipe, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of RCC is significantly influenced by the mechanical and physiochemical properties of cement, aggregate, water, and reinforcement, which significantly impact the quality of fresh and hardened concrete [5]. The grading of coarse aggregate strongly impacts concrete strength [6] and workability [7]; well-graded aggregate preserves workability better, while poorly-graded aggregate causes bond loss and segregation. The particle shape of the aggregate promotes stronger interlocking, which strengthens and prolongs the life of the concrete.…”
mentioning
confidence: 99%